Development of inflammatory bowel disease patient education and medical information sheets: serving an unmet need. Issue 7 (25th July 2022) - Al‐Ani, Aysha; Garg, Mayur
Abstract: Inflammatory bowel disease is a chronic gastrointestinal condition that necessitates life‐long healthcare engagement and management. Empowering patients with knowledge is fundamental to enhance health literacy, improve health outcomes and facilitate complex decision‐making regarding medication and potential surgery. A working group was formed to develop concise, comprehensive patient information sheets to meet this unmet need in the Australian setting.